2023
DOI: 10.24171/j.phrp.2022.0194
|View full text |Cite
|
Sign up to set email alerts
|

Association between the empirical dietary inflammatory index and musculoskeletal pain in community-dwelling older adults: a cross-sectional study

Abstract: Objectives: Inflammation has been proposed to be one of the main causes of musculoskeletal pain. Diet is a lifestyle factor that plays an important role in managing inflammation; thus, we assessed the inflammatory potential of diets using the empirical dietary inflammatory index (EDII) to investigate the relationship between diet and musculoskeletal pain.Methods: This cross-sectional study included 212 elderly individuals who were selected from health centers in Tehran, Iran. Dietary intake was evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, it's crucial to note that not all studies support these findings. A cross-sectional study among elderly Iranians found no significant correlation between the dietary inflammatory index and musculoskeletal pain 51 . In contrast, a more extensive cohort study in Spain, with a substantial sample size and an average follow-up period of 3.2 years, reported a significant association between an increase in the DII and pain events.…”
Section: Discussionmentioning
confidence: 95%
“…However, it's crucial to note that not all studies support these findings. A cross-sectional study among elderly Iranians found no significant correlation between the dietary inflammatory index and musculoskeletal pain 51 . In contrast, a more extensive cohort study in Spain, with a substantial sample size and an average follow-up period of 3.2 years, reported a significant association between an increase in the DII and pain events.…”
Section: Discussionmentioning
confidence: 95%
“…The sum of these scores provided the overall DII score. Energy-adjusted DII (E-DII™) scores, calculated per 1,000 kcal consumption using a density approach, followed a similar procedure but utilized an energy-adjusted global comparison database ( 2 , 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cardiovascular diseases (CVD) account for more than 30% of global deaths, with more than 18 million people dying from CVD-related conditions ( 1 ). Several studies have identified inflammation as the main underlying cause of CVD ( 2 , 3 ). A poor diet, which includes large quantities of calorically dense foods, rich in simple carbohydrates and fat, is known to be pro-inflammatory ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%